The Current Implementation of an Evidence-Based Hamstring Injury Prevention Exercise (Nordic Hamstring Exercise) among Athletes Globally - Wesam Saleh A. Al Attar (OVS LLC, 2021)
Purpose. The Nordic hamstring exercise (NHE) has been shown to be successful in reducing hamstring muscle injury (HMI), which is one of the most common non-contact injuries of the lower limbs. This is especially pertinent in sports that require acceleration, maximal sprints, and sudden changes in the direction of running and sprinting, such as soccer and rugby. This study aimed to evaluate the awareness, implementation, and opinions of athletes worldwide regarding the effectiveness of NHE in preventing hamstring injury. Materials and methods. A self-administered questionnaire was distributed to 1500 athletes from different sports. The survey consisted of six questions covering country, gender, type of sport, awareness, implementation, and opinions of athletes worldwide regarding the effectiveness of NHE in preventing hamstring injury. The survey was available in ten different languages. Results. A total of 1142 male and female athletes from different sports participated in the survey. More than half of the athletes 641 (56%) were aware of NHE, and only 519 (45.4 %) were implementing NHE in their current training routines. Athletes who implemented NHE reported a positive opinion regarding the program's effectiveness with a score of 8.4 ± 1 out of 10. Conclusions. Many athletes were aware of NHE and implemented it in their training routine since they found it to be effective in decreasing hamstring injury rates. However, additional work must be done to educate athletes about the importance of implementing this exercise and its effectiveness in preventing hamstring injury.